Novozym-435 as efficient catalyst for the synthesis of benzoic and (hetero)aromatic carboxylic acid esters. Issue 18 (6th May 2015) - Giunta, Daniela; Sechi, Barbara; Solinas, Maurizio
Abstract: Hereby we report new reaction conditions to convert benzoic acids and more general (hetero)aromatic carboxylic acids into the corresponding n -heptyl esters by applying Novozym-435 as the biocatalyst in cyclohexane as the solvent. Very good yields are obtained in the esterification of a plethora of substituted acids with mild and straightforward reaction conditions. Direct esterification of the acid is favoured compared to transesterification of methyl benzoate under our reaction conditions in all cases studied. Recycling of the immobilised enzyme is feasible although with some minor limitations. Graphical abstract: